Multifocal epithelial hyperplasia: an understudied infectious disease affecting ethnic groups. A mini review - Conde-Ferráez, Laura; González-Losa, María del Refugio (Frontiers in Cellular and Infection Microbiology, 2024)
Focal Epithelial Hyperplasia or Multifocal Epithelial Hyperplasia (MEH), also known as Heck’s disease, is considered a rare pathology of the oral mucosa associated with human papillomavirus types 13 and 32. For reasons not fully understood, MEH disproportionally affects specific populations of indigenous groups around the world. After the first reports in Native Americans, the epidemiology of the disease has been described in different geographical regions mainly related to particular indigenous populations, the majority of the studies are clinical case reports, but the biological determinants are still unknown. Some suggested risk factors include chronic irritation caused by smoking, a galvanic current, vitamin A deficiency, and/or a familial-genetic predisposition; however, the scientific evidence is not solid due the scarcity of case-control studies or longitudinal cohorts. In light of the evidence, further study of the pathology of MEH should be considered and proper clinical trials for effective treatments should be designed. The disease warrants further study as it is considered as neglected by research and it affects rural/remote population groups usually living in adverse socioeconomic conditions.